IVIM-DWI of transplanted kidneys: reduced diffusion and perfusion dependent on cold ischemia time - Rheinheimer, Stephan; Morath, Christian; Zeier, Martin; Kauczor, Hans-Ulrich; Hallscheidt, Peter (European journal of radiology, 2012)
Purpose To evaluate the effect of cold ischemia time (CIT) of renal allografts on diffusion and perfusion using intravoxel incoherent motion (IVIM) derived parameters. Material and methods A total of 37 patients with renal allografts (CIT: 27 <15h, 10 ≥15h) and 30 individuals with healthy kidneys were examined at 1.5T using a single-shot echo-planar diffusion-weighted pulse sequence with nine b-values ranging from 0 to 800s/mm2. ADC, perfusion fraction f, and the diffusion coefficient D were calculated using the IVIM model. Parameters of allografts stratified by CIT were compared with healthy kidney groups using the Mann-Whitney U test for unpaired data. We computed the Spearman correlation coefficient for correlation with creatinine values. Results ADC, D, and f of transplanted kidneys were significantly lower than in the healthy controls. The long-CIT group showed significantly lower diffusion parameters compared with the short-CIT group [mean±SD]: ADC: 1.63±0.14μm2/ms, f: 11.90±5.22%, D: 1.55±0.25μm2/ms versus ADC: 1.79±0.13μm2/ms, f: 16.12±3.43%, D: 1.73±0.14μm2/ms, PADC, f, D<0.05. Conclusion Our results suggest that diffusion parameters, especially the ADC, depend on the CIT of the kidney allograft. Potentially, this stands for functional changes in renal allografts. Diffusion-weighted imaging could be used for follow-up examinations. Thus, diffusion parameters may help guide therapy in patients with delayed graft function.